Panggung Politik Bali Kuno Pada Masa Pemerintahan Sri Maharaja Jayapangus - Srijaya, I Wayan; Dedy Prawirajaya R., Kadek (Humanis; Vol 27 No 3 (2023), 2023)
Inscriptions are a cultural heritage found in Java, Bali and Sumatra. They were written using stone, metal, clay and palm leaves. Judging from the language and letters used, there are inscriptions written in Old Balinese letters and languages, Old Javanese letters and languages, Old Malay letters and languages and a mixture of Pre-Negari and Sanskrit letters. This research aims to explain the political history during the reign of King Sri Maharaja Haji Jayapangus in Bali during the XII century. The data sources in this research are ancient Balinese inscriptions issued by King Jayapangus during his reign, in the XII century. The data were collected using interview and literature study methods and analysed using a descriptive analitical method. The results show that the inscriptions generally contain aspects of Balinese society and important past events. The reason for selecting the inscriptions issued during the reign of King Jayapangus is because the king is known to be very active in documenting various events in the form of inscriptions. According to records, no less than 44 inscriptions were issued by the king. One of the aspects mentioned in his inscriptions is the socio-political life. This aspect is important for further study, because it concerns the continuity of the government system that took place at that period.